Study on Physical and Mechanical Characteristics of Shear Band in Jinpingzi Landslide Region II - Wu, Yongjin; Huang, Shuling; Liu, Ke; Zhang, Qing; Pan, Hongyue (Frontiers in Physics, 2022)
The shear band is an important portion of a landslide. Investigating the shear band’s physical characteristics is one of the most significant challenges for landslide stability analysis and control. A systematic study of shear band in Jinpingzi landslide region II was conducted in this paper. The microscopic composition, deformation, strength, and creep characteristics are investigated by various experiments. In addition, CT visualization technology is utilized to monitor and scan the failure process of the shear band in real-time, as well as carry out studies on failure mechanisms. Furthermore, a constitutive model of the shear band is established as an alternative to the conventional Duncan and Chang model, which does not have this model’s limitations. The associated research will broaden understanding of such a medium's properties, but it will also be highly useful for stability analysis, deformation prediction, and prevention of such soil-rock mixture landslides.